Exploring posttraumatic growth in Tamil children affected by the Indian Ocean Tsunami in 2004. (13th October 2016) - Exenberger, Silvia; Ramalingam, Panch; Höfer, Stefan
Abstract : Few studies explore posttraumatic growth (PTG) in children from Eastern cultures. To help address this gap, the present study examined PTG among 177 South Indian children aged 8–17 years who were affected by the 2004 Tsunami. The study identifies the underlying factor structure of the Tamil version of the Revised Posttraumatic Growth Inventory for Children (PTGI‐C‐R), and aims to explore the prevalence of PTG, the relationship between distress and growth, and gender and age differences in PTG. The results of the principal component analysis indicated a two‐factor structure with an interpersonal and a person‐centred dimension of growth. The total scores of the Tamil PTGI‐C‐R were positively associated with posttraumatic stress symptoms (PTSS) and age. Moreover, there was a significant relationship between age and the person‐centred growth subscale. Non‐parametric tests found no gender differences in perceived growth. The role of socio‐cultural factors on the nature of PTG is discussed.